PERLINDUNGAN HUKUM TERHADAP PEMALSUAN MEREK DAGANG TERKENAL ASING DI INDONESIA - Moh Nafri (Maleo Law Journal, 2018)
Legal Protection Against Counterfeiting of Foreign Famous Trademarks in Indonesia". The problem under study is how the legal protection against foreign trademark counterfeiting in Indonesia and what are the factors inhibiting the implementation of brand protection against foreign trademark counterfeiting. The research used is normative law research method. The normative legal research approach is to examine the rules relating to research, namely the rules on legal protection against trademark counterfeiting. The results of the study found that legal protection is required for a brand that has obtained a notable predicate protected from imitation or forgery by others. Then the form of legal protection is a preventive and repressive. As for the factors that impede the implementation of the protection of the right of the brand that is the limitations of information to the public (consumer) on the existence of the application for registration of the mark, the difficulties of the holder of the right to foreign famous brand to find the perpetrator of the breach of the brand and the claim of the holder of foreign famous trademark in some respects worsens the reputation of the product because it is considered a problematic product.Keyword : Legal Protection, Counterfeiting, Foreign Famous Brand